PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN PUBLIK MELALUI MOTIVASI KERJA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Febriani Fitria; Marzolina Marzolina; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aimed to examine the influence of Leadership and Work Discipline onthe Quality of Public Services through Work Motivation in the Department ofPopulation and Civil Registration in the city of Pekanbaru. This study uses aquantitative approach. The sample in this study was 100 employees at theDepartment of Population and Civil Registration in the city of Pekanbaru.Sampling using the Saturated sampling technique method. The research instrumentused a questionnaire and was analyzed using path analysis using SPSS. The resultsof the study show that 1) There is a positive and significant influence betweenleadership and the quality of public service, 2) There is a positive and significantinfluence between work discipline and the quality of public service, 3) There is apositive and significant influence between work motivation and service qualitypublic, 4) There is a positive and significant influence between leadership and thequality of public services through work motivation, 5) There is a positive andsignificant influence between work discipline and the quality of public servicesthrough work motivation. Keywords : Leadership, Work Discipline, Work Motivation and Public ServiceQuality